Patient-Specific 3-Dimensional Model of Smooth Muscle Cell and Extracellular Matrix Dysfunction for the Study of Aortic Aneurysms. (August 2021) - Bogunovic, Natalija; Meekel, Jorn P.; Majolée, Jisca; Hekhuis, Marije; Pyszkowski, Jakob; Jockenhövel, Stefan; Kruse, Magnus; Riesebos, Elise; Micha, Dimitra; Blankensteijn, Jan D.; Hordijk, Peter L.; Ghazanfari, Samaneh; et al.
Introduction: Abdominal aortic aneurysms (AAAs) are associated with overall high mortality in case of rupture. Since the pathophysiology is unclear, no adequate pharmacological therapy exists. Smooth muscle cells (SMCs) dysfunction and extracellular matrix (ECM) degradation have been proposed as underlying causes. We investigated SMC spatial organization and SMC-ECM interactions in our novel 3-dimensional (3D) vascular model. We validated our model for future use by comparing it to existing 2-dimensional (2D) cell culture. Our model can be used for translational studies of SMC and their role in AAA pathophysiology. Materials and Methods: SMC isolated from the medial layer of were the aortic wall of controls and AAA patients seeded on electrospun poly-lactide- co -glycolide scaffolds and cultured for 5 weeks, after which endothelial cells (EC) are added. Cell morphology, orientation, mechanical properties and ECM production were quantified for validation and comparison between controls and patients. Results: We show that cultured SMC proliferate into multiple layers after 5 weeks in culture and produce ECM proteins, mimicking their behavior in the medial aortic layer. EC attach to multilayered SMC, mimicking layer interactions. The novel SMC model exhibits viscoelastic properties comparable to biological vessels; cytoskeletal organization increases during the 5 weeks in culture; increased cytoskeletal alignment and decreased ECM production indicate different organization of AAA patients' cells compared with control. Conclusion: We present a valuable preclinical model of AAA constructed with patient specific cells with applications in both translational research and therapeutic developments. We observed SMC spatial reorganization in a time course of 5 weeks in our robust, patient-specific model of SMC–EC organization and ECM production.